CORTICAL PLASTICITY AND ITS IMPLICATIONS FOR FOCAL HAND DYSTONIA - Opavsky, Robert; Hlustik, Petr; Kanovsky, Petr (Biomedical papers, 2006)
Background: The exact origin of focal dystonias has not been elucidated so far. Aberrant plasticity of the brain cortex is suspected to be a crucial factor in the development of this group of movement disorders. The aim of this article is to summarize recent findings on the etiopathogenesis of focal hand dystonias with a focus on the role of abnormal cortical plasticity.Methods And Results: A search of the literature mainly from 1995 to 2005 was done using the PubMed and Ovid search engines. English-language articles were identified using the following keywords: focal hand dystonia or writer's cramp and cortical plasticity, sensorimotor, imaging. Additional references were found through bibliography reviews of relevant articles. The data from neurophysiological and imaging studies, as well as clinical observation, in focal hand dystonia suggest multiple failures at different levels of the somatosensory and motor systems, particularly in the brain cortex. This disorders lead to attenuation of inhibitory and fortification of excitatory processes.Conclusions: The emerging theory presumes that a maladaptive plasticity of brain cortex with abnormal sensorimotor intergration can evolve in predisposed individuals. Consequent methods of management of focal hand dystonias are outlined.
Keywords: Focal hand dystonia/Cortical plasticity/Sensorimotor integration/Botulinum toxin